Exosomes Derived From Umbilical Cord Mesenchymal Stem Cells Treat Cutaneous Nerve Damage and Promote Wound Healing - Zhu, Ziying; Zhang, Xiaona; Hao, Haojie; Xu, Heran; Shu, Jun; Hou, Qian; Wang, Min (Frontiers in Cellular Neuroscience, 2022)
Wound repair is a key step in the treatment of skin injury caused by burn, surgery, and trauma. Various stem cells have been proven to promote wound healing and skin regeneration as candidate seed cells. Therefore, exosomes derived from stem cells are emerging as a promising method for wound repair. However, the mechanism by which exosomes promote wound repair is still unclear. In this study, we reported that exosomes derived from umbilical cord mesenchymal stem cells (UC-MSCs) promote wound healing and skin regeneration by treating cutaneous nerve damage. The results revealed that UC-MSCs exosomes (UC-MSC-Exo) promote the growth and migration of dermal fibroblast cells. In in vitro culture, dermal fibroblasts could promote to nerve cells and secrete nerve growth factors when stimulated by exosomes. During the repair process UC-MSC-Exo accelerated the recruitment of fibroblasts at the site of trauma and significantly enhanced cutaneous nerve regeneration in vivo. Interestingly, it was found that UC-MSC-Exo could promote wound healing and skin regeneration by recruiting fibroblasts, stimulating them to secrete nerve growth factors (NGFs) and promoting skin nerve regeneration. Therefore, we concluded that UC-MSC-Exo promote cutaneous nerve repair, which may play an important role in wound repair and skin regeneration.